About The Holy Steps of Samarkand - Azizkulov Akram Abduraxmonovich (Peerian Journals Publishing, 2023)
This article describes the educational significance of the objects of pilgrimage tourism in Samarkand region, in particular, the shrine of Imam Ali Sogdi. The article also contains information about Imam Ali Sogdi, who was recognized as the great Imam of his time
Keywords: Pilgrimage tourism; Samarkand region; Islamic theology